Creating a learning society a new approach to growth, development, and social progress - Stiglitz, Joseph (New York Columbia University Press, 2014)
It has long been recognized that an improved standard of living results from advances in technology, not from the accumulation of capital. It has also become clear that what truly separates developed from less-developed countries is not just a gap in resources or output but a gap in knowledge. In fact, the pace at which developing countries grow is largely a function of the pace at which they close that gap.
Includes bibliographical references (pages 589-623) and index.
Keywords: Social learning